Problematika Pembelajaran Pendidikan Agama Islam di SMA Muhammadiyah Imogiri Bantul - Sujadi (PAI 15 UMY 035, 2015)
*35 Problematika Pembelajaran Pendidikan Agama Islam di SMA Muhammadiyah Imogiri Bantul